Cross-Cultural Influences on Management Practices in Chinese Companies in Zimbabwe: Views from Non-Management - Muzvondiwa, Eresi; Msipah, Nothando; Nzero, Ignatious; Mukuze, Kabiat (Indonesian Journal Of Business And Economics, 2024)
ABSTRACTThis study explores how the cross-cultural influences management practices of Chinese companies operating in Zimbabwe, employing a qualitative research approach and a case study design. Focusing on two Chinese companies, the researchers conducted semi-structured interviews with 18 non-management employees. Non-management employees have unique perceptions that reflect their personal experiences and cultural context. Their viewpoints differ significantly from those of management, who might interpret practices through a lens shaped by their roles and responsibilities.Thematic analysis revealed significant findings regarding the impact of traditional Chinese cultural values, particularly Confucianism, on management practices. While hierarchical structures promoted clarity, they also stifled creativity and open communication, leading to employee frustration. Participants expressed a preference for collectivism but highlighted the challenge of balancing individual aspirations with group goals, resulting in feelings of underappreciation. Additionally, perceptions of top-down management and cultural misunderstandings, particularly regarding communication styles and concepts of time, emerged as critical barriers to effective management. Participants advocated for a more inclusive management approach that recognizes individual contributions and fosters constructive dialogue. The study emphasizes the need for cultural awareness and training to bridge communication gaps and enhance organizational cohesion. By illuminating these cross-cultural dynamics, this research contributes to a deeper understanding of management practices in a globalized context, offering insights into how Chinese companies can adapt their strategies to better align with Zimbabwean employees' expectations.Keywords: Cross-culture, Confucianism, Chinese companies, Employees’ perceptions, Management practices